Edukasi Penggunaan Obat Simptomatik Dan Antibiotik Terhadap Suatu Penyakit Kepada Siswa SMAS Primbana Medan - Simorangkir, Delisma; Sanjaya, Angga (INSTITUT KESEHATAN DELI HUSADA, 2023)
This article is an analysis of education regarding the use of symptomatic drugs and antibiotics for a disease for SMAS Primbana Medan students. Education on the use of symptomatic drugs and antibiotics for a disease is an important thing to educate students and the public to provide appropriate information on the good and appropriate use of symptomatic drugs and antibiotics, because of the high number of side effects in the use of symptomatic drugs and antibiotics in the community, one One side effect that occurs when using symptomatic drugs is stomach ulcers and when using antibiotics, namely antibiotic resistance. PKM activities are carried out in three stages, namely the production implementation stage, the evaluation stage and the reporting stage. PKM activities are useful for increasing public health knowledge and standards where students can participate in educating friends, family and the environment about when to use symptomatic drugs and antibiotics and when to stop using them.